Trends in migration between different settlement types: Turkey, 1965-90 - Ayse Gedik (European Regional Science Association (ERSA), 1998)
Migration between different settlement types and the resultant national population distribution have significant effects on the various socio-economic factors and on the national development indices: such as education levels, fertility rates, infant mortality rates, women's development and rights, and the type of economic activity,etc. This is particularly relevant for the developing countries. The purpose of this paper is to describe the macro trends and the related changes in the internal migration in Turkey between different three settlement types according to the administrative definition: i.e., villages, district centers, (towns), and the province centers (urban cen. Descriptive analysis is carried out by indicating the changes and the sources of these changes through the 1965-90 period: (1) changes in the population sizes of the different settlement types; (2) net migration as the source of these population changes; (3) origins and destinations of the net migrants; (4) in- and out-migration as two components of the net migration; and (5) plausible hypotheses for the underlying patterns. The migrant is defined as those who changed their "permanent residency" during five-years between two consecutive population census days. The data are from the Population Censuses (P.C.) of 1970, 80, 85, and 90. Thus it covers the four five-year periods of 1965-70, 75-80, 80-85, 85-90.
Keywords: 330